Error simulation in a maturity environment for software engineering teaching - Begosso, Luiz Carlos (2006)
The software industry blames universities for their graduates lacking necessary skills, meaning that just the possession of knowledge does not necessarily imply the competent performance required by the profession. Professional maturity in software engineering is one of software industry’s major needs and in-office training can not address this need as efficiently as university education can. This paper exposes the experience reached in a software engineering course in which students develop their software projects in a mature environment. The emphasis here is to use a tool inside a maturity environment that can simulate user errors when operating the software, so that students can learn how to prevent them in their software projects.